Development of excellent and novel flowery zirconia/cadmium sulfide nanohybrid electrode: For high performance electrochemical supercapacitor application. (August 2021) - Manzoor, Sumaira; Ashiq, Muhammad Faheem; Usman, Muhammad; Sadaqat, Maira; Mahmood, Khalid; Munawar, Tauseef; Iqbal, Faisal; Al-Anazy, Murefah Mana; Ashiq, Muhammad Naeem; Najam-ul-Haq, Muhammad
Highlights: CdS nanowires folded in ZrO2 sheets to form flowery ZrO2 /CdS nanohybrid synthesized via coprecipitation route. ZrO2 /CdS nanohybrid based electrode material exhibited high pseudo specific capacitance (1391F/g) at a current density of 2.5A/g. The electrode material showed high energy density (48.27 Wh/Kg) and cyclic stability (2000 cycles). ZrO2 based ZrO2 /CdS nanohybrid can be engaged as a significantly remarkable material deposited on NF electrode for pseudo supercapacitor devices. Abstract: The energy storing devices such as batteries as well as super-capacitors are limited due to poor electrochemical performance and less cycling stability of electrode materials. To achieve significantly high performance and stability which are critical criteria for examining an electrode material for supercapacitor applications, the production of nanostructured materials for improving specific surface area and electrical conductivity is very crucial. In present work, simple and economical coprecipitation route is used to synthesize ZrO2 /CdS nanohybrid. Structure, chemical composition, oxidation state and morphology of the synthesized materials i.e. ZrO2, CdS and ZrO2 /CdS nanohybrid were seasoned via X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), X-ray photoelectron spectroscopy (XPS) and scanning electron microscopy (SEM), transmission electron microscopy (TEM), respectively. Energy dispersive x-ray spectroscopy (EDX) was used to confirm the elemental composition of all prepared materials. The incorporation of CdS nanowires in ZrO2 sheets improves the morphology of the nanohybrid. Due to improved morphology, the nanohybrid (ZrO2 /CdS) showed a remarkable stability (2000 cycles), specific capacitance (1391F/g) and specific energy (48.27 Wh/Kg) at a current density of 2.5A/g measured via three electrode galvanostatic charge discharge (GCD) system. Additionally, extraordinary electrochemical performances of ZrO2/CdS nanohybrid have remarkable technological applications in future. Graphical abstract: Image, graphical abstract